Satiety and consumers' perceptions: What opinions do Argentinian and Brazilian people have about yogurt fortified with dairy and legume proteins? - Curti, Carolina Antonela (2022)
This study (1) evaluated the perceptions of Argentinian and Brazilian consumers regarding yogurt fortified with dairy proteins, legume proteins, or a combination of both, and (2) determined the satiety expectations of these foods as well as the consumers' intentions to taste and purchase protein-fortified yogurt. A total of 298 Argentinian and 100 Brazilian participants completed an online survey for this study. The free word association technique was used to investigate their perceptions about “satiety” as a verbal stimulus and 6 concepts of yogurt as visual/verbal stimuli (yogurt, set yogurt, skim set yogurt, skim set yogurt with a high content of dairy proteins, skim set yogurt with a high content of legume proteins, and skim set yogurt with a mix of dairy and legume proteins). The expected satiation and intentions to taste or purchase were evaluated using categorical scales. Regardless of their cultural background, participants from both countries expressed similar associations with the stimuli presented. Yogurt and set yogurt were associated with consumption occasions, sensory characteristics, liking, and foods, whereas skim yogurt was associated with diet food. Products fortified with proteins were associated with healthy foods, regardless of the protein source, and they yielded the highest rates for expected satiation. Brazilian participants were more likely to taste the food with a combination of proteins; however, participants from both countries were indifferent to purchasing the product. Important characteristics in the design and marketing of these products were pleasant sensations, such as “fullness,” “satisfied,” and snacks to eat “on the go,” and the vegetarian consumers' segment. The combination with fruits or cereals, creaminess, and vanilla flavor should also be considered. The study findings could have implications for the dairy industry when designing yogurt fortified with proteins and communicating the nutritional and wholesome properties of these products.